SOME APPLICATIONS OF SEPARATION AXIOMS ON ROUGH SETS - A. I. EL-MAGHRABI, SAEID JAFARI,RAJA MOHAMMAD LATIF,A. M. MUBARAKI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Rough set theory is one of the new methods that connect information systems and data processing to mathematics in general and especially to the theory of topological structures and spaces.This paper is aimed to improve some new types of separation axioms by using the concept of sets. So, we define new separation axioms called Also, some of its properties are investigated. Further, we defined space and studied the relation between this space and some types of mappings. Furthermore, we introduce spaces and several properties of this space are presented